ANALISIS EKSPOR DAN IMPOR DALAM MENINGKATKAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI PROVINSI NUSA TENGGARA BARAT - Baiq Kisnawati; Irianto Irianto; Rusli Amrul (Nusantara Hasana Journal, 2022)
This study aims to determine the development of exports and imports in increasing gross regional domestic product (GRDP) in the province of West Nusa Tenggara from 2016 to 2020. This research is classified as a descriptive study consisting of three independent or independent variables, namely export, import and product variables. gross regional domestic. Index number analysis is used to see how the development of exports and imports in increasing GRDP. The results showed that for five years, the index for exports averaged 38.62 per year, meaning that the export value decreased by 61.38% per year. The average import index figure is 116.69% per year, meaning that the import value has increased by 16.69% per year. Although the value of imports has increased, net exports are still positive because the value of exports is higher than the value of imports. The net export index figure shows a figure of 29.39% per year, meaning that there is a decline in net exports by 70.61% per year. The GRDP index figure shows an average of 110.26% per year, meaning that GRDP has increased by an average of 10.26% per year. An increase in exports will directly increase GRDP, but on the other hand, an increase in GRDP does not necessarily increase the value of exports. This study shows that the export value has decreased quite high but the GRDP continues to increase because there are other sectors that experience development/increase from year to year.